Molecular Characterization And Comparison Of Multi Drug Resistant Strains Of Mycobacterium Tuberculosis By Phenotypic And Genotypic Method - Bhatt, CP; Bhatt, AB; Shrestha, B (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: Drug resistant tuberculosis is a signifi cant threat to tuberculosis control because only a few effective drugs are available against M. tuberculosis. The aims of this study were to compare multi drug resistant (MDR) strains of tuberculosis by phenotypic and genotypic method and determine type, location and frequency of rpoB and KatG gene mutations. Methodology: Anti-tuberculosis drugs susceptibility test of M. tuberculosis grown on Lowenstein Jensen medium was performed by proportion method. MDR cases were analyzed for mutation of rpoB and KatG genes. The regions of these genes were amplifi ed by polymerase chain reaction (PCR) and sequenced. Results: Two different mutations were identifi ed in rifampicin resistant strains. The most common point mutations were in codons TCG 531→TTG (85%) and GAC 516→TTC (15%) of the rpoB gene. Two different mutations in KatG gene were detected. The most common KatG point mutations were AGC 315 ACC (Ser→Thr) (85%) and CGG 463 CTG (Arg→Leu) (10%). In this study DNA sequencing analysis did not fi nd mutation on KatG gene of one of the strain tested. Male and female were equally affected by MDR tuberculosis and majorities (35%) of them were found in 21-30 years age group. Conclusion: The present investigation agrees that genetic mutation is responsible for change in phenotypic characteristics of M. Tuberculosis. DOI: http://dx.doi.org/10.3126/saarctb.v8i2.5896 SAARCTB 2011; 8(2): 17-22